PENGARUH MULTILANE FREE FLOW TERHADAP KINERJA JALAN TOL - Ahmad Munawar; Imam Muthohar; Arif Ardiyanto (Himpunan Pengembangan Jalan Indonesia (HPJI), 2020)
Abstract Traffic congestion on toll roads generally occurs at toll gates. Therefore, it is necessary to plan the replacement of the toll payment system, from the Card Based Tolling System to the Multilane Free Flow with the Electronic Toll Collection System, which can improve toll road performance. In this study a simulation of improving toll road performance by applying Multilane Free Flow, with the use of VISSIM software. As a case study, Tebet 2 Toll Gate was chosen, because this toll gate is considered as one of the toll gates with a high traffic flow. In the Card Based Tolling System, the vehicle must stop to attach the card, whereas in the Multilane Free Flow with the Electronic Toll Collection System, the vehicle is quite slow when entering the toll gate. Simulation results indicate a significant increase in performance with this replacement. Queues, delays, fuel consumptions, and pollutants are significantly reduced. Keywords: toll gate, Multilane Free Flow, Electronic Toll Collection, Card Based Tolling System, queues, delays Abstrak Kemacetan di tol umumnya terjadi pada pintu gerbang tol. Oleh karena itu, perlu direncanakan penggantian sistem pembayaran tol, dari Card Based Tolling System ke Multilane Free Flow dengan Electronic Toll Collection System, yang dapat meningkatkan kinerja jalan tol. Pada studi ini dilakukan simulasi peningkatan kinerja jalan tol dengan menerapkan Multilane Free Flow, dengan bantuan perangkat lunak VISSIM. Sebagai studi kasus dipilih Pintu Tol Tebet 2, yang merupakan salah satu pintu tol dengan arus lalu lintas yang cukup tinggi. Pada Card Based Tolling System, kendaraan harus berhenti guna menempelkan kartu, sedangkan pada Multilane Free Flow dengan Electronic Toll Collection System, kendaraan cukup memperlambat pada saat memasuki pintu tol. Hasil simulasi menunjukkan adanya peningkatan kinerja yang signifikan dengan perubahan ini. Antrian, tundaan, penggunaan bahan bakar, serta pollutant berkurang secara signifikan. Kata-kata kunci: pintu tol, Multilane Free Flow, Electronic Toll Collection, Card Based Tolling System, antrian, tundaan